Active learning activities: “Escape Room” for first year students - Berggren, Lenita Brodin; Jorum, Ika (Septentrio Conference Series, 2021)
First year architecture students are introduced to the library by taking part in an “Escape Room” activity in the KTH library. The aim of this initiative is to introduce the students to the library space and the library ́s resources in an interactive and playful way and to enable them to learn and reflect upon their learning within the frame of an active learning activity.1 Another objective with this active learning introduction is to engage students in a collaborative peer-to-peer learning activity that gives them opportunities to share knowledge and solve problems together. In this presentation, we will talk about the introduction in more detail and discuss the benefits of the live-action method as well as share results and improvements. “Escape room” is a live-action game, developed from a computer game. Gamification is a new trend in education to support cooperation, learn by “doing” and develop new knowledge through a more playful way.2 During the workshop, the students worked in groups, which gave them the opportunity to socialize and learn from each other while solving the tasks on time.The results of the students’ assessment after the game indicates that the students enjoyed the game, the teamwork, the competition and the creativity of the introduction compared to a lecture. They also found it a pedagogical way of learning about the library’s resources. During the workshop,the librarians had the opportunity to adjust instructions that were not clear enough. These adjustments effected the comments in the last group where some answers indicated a wish for more difficult clues. 1 Brian Detlor et. al., “Student perceptions of information literacy instruction: The importance of active learnings”, Education for Information 29 (2012), https://doi.org/10.3233/EFI-2012-0924, 147-161 2 Cassano, Fabio, Antonio Piccinno, Teresa Roselli, and Veronica Rossano. “Gamification and Learning Analytics to Improve Engagement in University Courses”,Advances in Intelligent Systems and Computing 804 (2019),156-63